Organizational Impact of Knowledge Management on Innovation Intellectual Capital Research and Creativity: A Systematic Literature Review - Farhana Zahra; Dzakiyyah Al Kaazhim; Putri Luthfiah Harmaya; Muharman Lubis (RAM PUBLISHER, 2025)
Rapid changes in global competitiveness require organizations to manage knowledge as a strategic resource to improve innovation, intellectual capital, and creativity. This study explores the impact of Knowledge Management (KM) on organizational innovation by analyzing its relationship with intellectual capital and digital governance. The objective of the research is to examine how KM processes influence innovation performance, and how intellectual capital acts as a mediating factor in this relationship. The novelty of this study lies in its synthesis of KM, innovation, and intellectual capital through the lens of digital governance. The research uses a systematic literature review method by analyzing ten peer-reviewed articles published between 2020 and 2025, selected through the PRISMA 2020 protocol from databases such as Scopus, ScienceDirect, and Google Scholar. The findings show that KM enhances innovation when supported by strong human, structural, and relational capital, along with well-structured digital systems. This study contributes to the development of adaptive strategies for innovation-driven organizations based on integrated knowledge practices